Manajemen Berbasis Sekolah Untuk Meningktakan Kualitas Sekolah Yang Bercirikan Buddhis - haudi, haudi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The management of early childhood education units, basic education, and secondary education is carried out based on minimum service standards with school/madrasah-based management principles. The school management in question is a form of autonomy in the management of education in primary and secondary education units which shows independence, partnership, cooperation, participation, openness, and responsibility. Research on the implementation of SBM in the world of education has often been carried out with the evidence that many journals have been published. Some researchers focus on the leadership of principals, teachers and the quality of student education. There are no researchers who have paid attention to the implementation of SBM in schools with Buddhist characteristics, especially the implementation of Pancasila, the Sigalovada Sutta, and the Dasa Raja Dhamma. Therefore, the focus of this research is on the application of Buddhist values that are applied by teachers and students, in teaching and learning activities as well as in daily life. This study aims to determine whether DS schools have implemented SBM with Buddhist values. The research was conducted using descriptive qualitative analysis with primary data sourced from resource persons and key persons using interview, observation, and documentation methods. The sample taken in this study amounted to 9 informants. The results of the study show that SBM with Buddhist values is only implemented by students and some teachers, while teachers, school officials and administration still have not implemented SBM with Buddhist values